Income inequalities within couples in the Czech Republic and European countries - Martina Mysíková (Charles University in Prague, Institute of Economic Studies (IES), 2011)
This study analyses the income distribution within couples in the Czech Republic and ten European countries using the EU-SILC 2005 database. Data from the Luxembourg Income Study (LIS) database supplement the analysis with previous period (1986 - 2000). Women, on average, contribute less to a couple's income than men. Among the included countries, within-couple income inequality tends to be lower in the new EU member states than in the old ones, with the Czech Republic being the exception. Within-couple income inequality has two crucial factors: employment of female partners and, subsequently, their wages. In the context of the first, the inter-generational transmission of the traditional model of the family proved to have a significant negative impact on the female employment decision mainly in the old EU member states. Finally, gender wage gaps between men and women who live in a couple were examined and compared with the gender wage gaps for single individuals. The gender wage gap proved to be higher for cohabiting individuals than for singles even after adjusting for gender differences in individual and job characteristics.
Keywords: D19; J31; J79; 330; gender wage gap; traditional family model; within-couple inequalities; Lohndifferenzierung; Geschlecht; Lebensgemeinschaft; Weibliche Arbeitskräfte; Tschechische Republik; EU-Staaten